Home-made separation unit for colorimetric detection of ethanol in alcoholic beverages - Phomkeona, Kesiny; Inoue, Hayato; Chounlamany, Vanseng; Moxom, Phovilay; Phouthavong, Vanpaseuth (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This work described the utilization of a separation unit for colorimetric determination of ethanol (C2H5OH) in alcoholic drink samples. The unit was simply home-made from reused 40-mL glass nutrition drink bottles. It consisted of a sample container, hanging from the bottle lid, and an acceptor (in this case dichromate solution (Cr2O72˗)) container, which was the bottle body itself. The alcoholic drink sample was directly injected to the sample container via the bottle lid using a common plastic syringe. Ethanol in the samples spontaneously vaporized in the closed system and subsequently oxidized Cr2O72˗ (orange) to green chromium ion (Cr3+) inside the unit. After five minutes, the unit was opened to transfer the acceptor for measuring color change as absorbance at 590 nm, which corresponded to C2H5OH concentration using a UV-Visible spectrophotometer. The method was found to be applicable for analysis of C2H5OH in the range 1.0–90 %(v/v) with high accuracy (recovery 89 – 109 %), and satisfied precision. Ethanol contents in alcoholic beverage samples including beer, wine, whisky, and cider were quantified by this method, which were insignificantly different to those shown on product labels. The method has high potential for applying in analysis of C2H5OH in both colored and colorless liquid samples, with benefits of cheapness and simplicity.